An efficient wideband hafnia-bismuth erbium co-doped fiber amplifier with flat-gain over 80 nm wavelength span - Al-Azzawi, Alabbas A.; Almukhtar, Aya A.; Reddy, P.H.; Das, Shyamal; Dhar, Anirban; Paul, Mukul Chandra; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2019)
A new wideband erbium doped fiber amplifier (EDFA) is proposed and demonstrated, utilizing a newly fabricated hafnia-bismuth erbium co-doped fiber (HB-EDF) as a gain medium. The proposed amplifier is tested in both double-pass series and parallel configurations, using 22 cm and 150 cm long HB-EDFs to realize amplification in C and L-band wavelength region, respectively. Both series and parallel configurations obtained a wideband operation at wavelength region from 1520 to 1610 nm. At input signal power of −10 dBm, the parallel HB-EDFA achieved a flat gain of 12.1 dB with a gain ripple of less than 2 dB, along the wavelength region of 80 nm from 1525 to 1605 nm. Within the flat gain region, the noise figure was less than 11.8 dB. Overall, the parallel HB-EDFA has a better performance than the series HB-EDFA.